2016
DOI: 10.1016/j.arcped.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Portage parasitaire digestif d’enfants adoptés

Abstract: According to the results of this study, gastrointestinal parasites are still very frequent in stool samples from immigrant children. Since they are easy to transmit, the majority of infections were protozoan. The best antiparasitic strategy lies in: (a) the routine screening of stool from any immigrant child coming from endemic areas and (b) the use of antiparasitic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…As described in other series [ 25 , 26 , 27 , 28 ], the most prevalent infections in our patients were intestinal parasitosis (8/57), followed by a positive serology result for schistosomiasis (7/40), strongyloidiasis (3/49), or toxocariasis (3/49). Upon arrival in the new home country, the screening of infectious diseases must be individualized and tailored to the origin and previous living conditions.…”
Section: Discussionsupporting
confidence: 80%
“…As described in other series [ 25 , 26 , 27 , 28 ], the most prevalent infections in our patients were intestinal parasitosis (8/57), followed by a positive serology result for schistosomiasis (7/40), strongyloidiasis (3/49), or toxocariasis (3/49). Upon arrival in the new home country, the screening of infectious diseases must be individualized and tailored to the origin and previous living conditions.…”
Section: Discussionsupporting
confidence: 80%
“…Our results confirm that not all PIs are associated with eosinophilia. Although an increase in peripheral blood count is more frequently associated with helminthic infections [ 30 , 31 , 32 , 33 ], this usually occurs when the parasite invades the host’s tissues. Widespread parasitosis such as Giardia lamblia infection, which our study reported affecting 12.6% of the IAC, are intraluminal and, therefore, are not associated with eosinophilia [ 1 ].…”
Section: Discussionmentioning
confidence: 99%